THE EFFECT OF ENVIRONMENTAL PERFORMANCE ON COMPANY VALUE WITH FINANCIAL PERFORMANCE AS INTERVENING VARIABLE AT THE MANUFACTURING COMPANY LISTED IN INDONESIA STOCK EXCHANGE - Eka Miratul Khasanah; Teddy Oswari (Universitas Gunadarma, 2019)
Environmental problems have become a central issue for several countries around the world, especially in Indonesia and become a concern to the various parties, including government, public, even the accounting disciplines. The reason is that Indonesia has decreased in Environmental Performance Index and causes a lot of negative impacts, not only for the community itself but also the company that takes the raw material from nature for their production activity. This study aimed to investigate the effect of environmental performance on company value directly and indirectly through financial performance as an intervening variable. The object is some manufacturing companies listed in Indonesia Stock Exchange from 2011-2014. This study used purposive sampling to determine the sample, that generates 20 manufacturing companies as a study sample. Data used in this study is secondary data obtained from the annual report and PROPER Assessment Report. This method used path analysis to see the direct and indirect effect between the independent variables with the dependent variable. The results showed that environmental performance does not give significant effect on company value, while environmental performance gives a significant effect on financial performance, financial performance gives a significant effect on company value, and environmental performance has a significant effect on company value through financial performance as intervening variables. Furthermore, financial performance is intervening variables that may mediate the relationship between environmental performance and company value.